Analisis Manajemen Risiko Kredit Usaha (KUR) Untuk Meminimalkan Kredit Bermasalah - Faradila Indah Sucianty; Gusgana Suria Manda (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to analyze the application of credit risk management from MSMEs to the People's Business Credit (KUR) of Bank BJB to minimize bad loans and find effective applications. This type of survey uses a descriptive survey method. The results showed that Bank BJB actively controls the commissioners and the board for credit risk management, policies, procedures, restrictions, identification, measurement, monitoring, and information systems. This study shows that Bank BJB can maintain staff independence in lending and can be very effective in improving the credit monitoring process.